Assessment of nutritional status of children aged 34-92 months using various nutritional status indices and validity of age independent indices - Gandra, Nayantara R.; Masillamoni, Kalavathy Jasmine (International Journal of Contemporary Pediatrics, 2019)
Background: Even though there are many programs run by Government to tackle the problem of malnutrition in India, problem of malnutrition is still there. Malnutrition leads to infections and even can lead to death of child in severe cases. The mortality rate is very high compared to other countries. The objective of the study to study validity of age independent various nutritional status indices in comparison to gold standard of weight for age Methods: Present study was institution based cross sectional study carried out at SDA high school, from January 2019 to July 2019 among 58 school children aged 34-92 months of age. Anthropometric measurements like weight, height, head circumference, chest circumference, mid arm circumference were recorded as per the standard guidelines. Weight for height, weight of age, Kanawati Index, Jeliffe’s ratio, Rao index, and Dugdales index was calculated. Gold standard used was weight for age. Sensitivity, specificity, positive predictive value and negative predictive value were calculated for these indices. Results: Majority of the children belonged to 48-60 months and 61-72 months i.e. 29.3% each. Males were more than females. Prevalence of malnutrition was 60.3%, 48.3%, 51.7%, 91.4%, and 56.8% based on weight for age, Kanawati index, Rao index, Jeliffe’s ratio and Dugdale’s index respectively. Dugdale’s index was found to have high sensitivity (85.7%) and specificity (86.9%) compared to all other indices. Conclusions: Among age independent indices of nutritional status available, Dugdales index can be used as it has been found that it has remarkably higher sensitivity and specificity compared to other age independent indices of nutritional status.